The change in Diesel Engine Oil Properties During Performance - Alani, Kafaa (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Infrared (IR) and Differential Scanning Calorimetric (DSC) analytical tests have been used to study the change in diesel engine oil properties during performance, in addition to the changes in physical and chemical properties. Two types of diesel engine oils (petroleum base) that are used in bus vehicles were examined in bus diesel engines travelling distances up to 5000 km. The results show the characterization of the oil as the changes in chemical composition and physical properties with the travelling distances increase. Also, the results show the changes that take place in the diesel engine oils during use up to 5000 km depend on choosing the type of oil that bears such heavy duty engines as the bus vehicle, and the period required to change the oil to avoid damage to the different parts of the engine.